Effect of some physiochemical treatments on seed germination of Palestine pistachio - جرجس مخول; وفاء علي عطاف (Latakia University Journal -Biological Sciences Series, 2022)
This research was carried out in the nursery of Tishreen University and the laboratories of the Faculty of Agriculture to study the effect of stacking, soaking with distilled water, concentrated sulfuric acid, and gibberellic acid, which are needed to germinate the Pistacia plalastina seeds and increasey its germination ratio. The results showed the following: The wet stratification at a temperature of (4 ± 2 C) before planting did not achieve the desired goal in raising the germination ratio of Palestinian pomegranate seeds. The germination rate did not exceed 6.67% in the stratification treatment for 90 days and 60 days before planting and (4.44%) in the stratification treatment for 45 days before planting and 2.22% in the control. The best germination ratio (84.44%) was obtained by application of treatment of seeds by soaking in distilled water for 24 hours, then soaking with gibberellic acid at a concentration of 500 ppm for 24 hours, and then stratification for 45 days before planting and it was significantly superior to all other treatments, followed by treating seeds with acid Concentrated sulfur for 60 minutes, then laying for 60 days before planting, soaking the seeds with concentrated sulfuric acid for 60 minutes, then soaking with gibberellic acid at a concentration of 500 ppm for 24 hours and stratification for 60 days with a germination ratio of 64.44% and 62.22% without any significant difference between them.